Diagnosis of naturally‐occurring Cushing's syndrome by primary care veterinarians in selected European countries - Miguel F. Carvalho; Rodolfo O. Leal; Stefania Golinelli; Federico Fracassi; Carolina Arenas; Maria Pérez‐Alenza; Sara Galac; Carmel T. Mooney; Michael Bennaim (Journal of Veterinary Internal Medicine)
Abstract Background Several tests are available to diagnose naturally‐occurring Cushing's syndrome in dogs but there is a paucity of information on how primary care veterinarians (PCVs) use or interpret them. Objectives Determine how PCVs from selected European countries diagnose Cushing's syndrome in dogs. Methods Cross‐sectional survey study assessing testing protocols used by PCVs for screening and differentiation of Cushing's syndrome. Results Two thousand one hundred and seventy‐eight responses from 9 European countries were included. When Cushing's syndrome was suspected, 98.7% of respondents perform endocrine testing, whereas 1.2% rely on a treatment trial. Among the former, 59.9% reported performing screening tests in the absence of supportive clinical signs but with consistent clinicopathological abnormalities. Of 2150 respondents who performed endocrine testing, 66.6% report always using the same initial screening tests regardless of their pretest suspicion of disease. The tests most reported are the ACTH stimulation test (34.8%), low‐dose dexamethasone suppression test (LDDST; 30.4%) or a combination of different tests (25.2%). In the absence of financial constraint, 1419 (66.0%) respondents always attempted differentiation, using abdominal ultrasonography (81.0%) and LDDST (46.1%). Overall, 69.8% of respondents reported offering referral to a specialist in ≤20% of cases suspected or diagnosed with Cushing's syndrome over the previous 5 years. Conclusions and Clinical Importance Testing protocols vary among PCVs. Almost 60% of respondents potentially screen dogs without consistent clinical signs, raising concerns for overdiagnosis. A proportion never attempt differentiation, which likely affects prognosis. Cases are rarely referred to a specialist, reflecting that Cushing's syndrome is mainly managed in primary care practices. These results suggest that there is room for further education of PCVs.